Circadian dysregulation induces alterations of visceral sensitivity and the gut microbiota in Light/Dark phase shift mice - Hu, Lilin; Li, Gangping; Shu, Yanyun; Hou, Xiaohua; Yang, Ling; Jin, Yu (Frontiers in Microbiology, 2022)
Background: It is well-established that several features of modern lifestyles, such as shift work, jet lag, and using electronics at night, disturb normal circadian rhythm and increase the risk of suffering from functional gastrointestinal disease. Notwithstanding that substantial evidence demonstrates that shift work is closely correlated with the symptoms of visceral hypersensitivity, few basic studies have revealed the mechanism of visceral hypersensitivity induced by circadian rhythm disturbance, especially light/dark phase shifts. Our study explored the mechanism underlying visceral hypersensitivity caused by light/dark phase shift in mice. Methods: A 6-hour delay light/dark phase shift mice model was constructed. Visceral hypersensitivity was assessed by abdominal withdrawal reflex (AWR) score induced by colorectal distention (CRD) in vivo and contraction of colonic muscle strips induced by acetylcholine ex vivo. Intestinal permeability was evaluated by transepithelial resistance (TEER) and FD4 permeability. The expression of tight junction proteins was detected by western blotting and immunofluorescence staining. The gut microbiota was examined by 16S rDNA sequencing. Fecal microbiota transplantation (FMT) was performed to confirm the relationship among the light/dark phase shift, gut microbiota and visceral hypersensitivity. Results: We found that light/dark phase shift increased visceral sensitivity and disrupted intestinal barrier function, caused low-grade intestinal inflammation. Moreover, we found decreased microbial species richness and diversity and a shift in microbial community with a decreased proportion of Firmicutes and an elevated abundance of Proteobacteria at the phylum level. Besides, after the light/dark phase shift, the microflora was significantly enriched in biosynthesizing tryptophan, steroid hormone, secondary metabolites, lipids, and lipopolysaccharides. Mice that underwent FMT from the light/dark phase shift mice model exhibited higher visceral hypersensitivity and worse barrier function. Dysbiosis induced by light/dark phase shift can be transmitted to the mice pretreated with antibiotics by FMT not only at the aspect of microbiota composition but also at the level of bacterial function. Conclusion: Circadian rhythm disturbance induced by light/dark phase shift produce visceral hypersensitivity similar to the pathophysiology of IBS through modulating the gut microbiota, which may disrupt intestinal barrier function or induce a low-degree gut inflammation.